Introduction to Dossier. Towards a Re-appropriation of Critical Geography for Latin America - Zaragocin Carvajal, Sofia; Moreano Venegas, Melissa; Álvarez Velasco, Soledad (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2018)
This article attempts to review and synthesise the main debates in critical geography across both the Latin American and Anglo-Saxon traditions. By reviewing the main theoretical approaches including from political ecology, feminist geography, post-colonial and de-colonial approaches and the geography of motilities and migration, the aim of this article is to delineate a pan-Latin American approach to critical geography. We also consider why some approaches and topics have received greater or lesser attention in Latin American scholarship. Finally, we emphasize the importance of establishing a new transnational dialogue based on regionally situated critical research that questions and proposes new pathways in the production of knowledge from and about the region. We suggest this approach be nested in critical theory and committed to local political and territorial struggles.